2008
DOI: 10.1002/bjs.6393
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year results of a randomized clinical trial of laparoscopic total fundoplication with or without division of the short gastric vessels

Abstract: When total fundoplication is performed it makes no difference whether the fundus is mobilized or not. Both types of repair provide lasting control of reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…In a precedent report the same authors have reported subtle manometric differences between the two study groups, offering a physiologic background to a potential difference in functional outcome (Engstrom et al 2004), but it appears that these differences in lower esophageal sphincter response to gastric distension with air do not translate into important and clinically relevant functional correlates. At 10 years follow-up, the authors concluded that with total Fundoplication it makes no difference whether the fundus is mobilized or not and that both types of repair provide long-lasting control of reflux (Mardani et al 2009 (Leggett et al 2000). All patients experienced relief from symptomatic gastroesophageal reflux, whether they received the Rossetti modification or the Nissen Fundoplication.…”
Section: Division Versus Non Division Of the Short Gastric Vesselsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a precedent report the same authors have reported subtle manometric differences between the two study groups, offering a physiologic background to a potential difference in functional outcome (Engstrom et al 2004), but it appears that these differences in lower esophageal sphincter response to gastric distension with air do not translate into important and clinically relevant functional correlates. At 10 years follow-up, the authors concluded that with total Fundoplication it makes no difference whether the fundus is mobilized or not and that both types of repair provide long-lasting control of reflux (Mardani et al 2009 (Leggett et al 2000). All patients experienced relief from symptomatic gastroesophageal reflux, whether they received the Rossetti modification or the Nissen Fundoplication.…”
Section: Division Versus Non Division Of the Short Gastric Vesselsmentioning
confidence: 99%
“…Mardani, Lundell and colleagues designed a randomized controlled trial to determine the long-term results of total Nissen Fundoplication with or without division of short gastric vessels in a 10 years follow-up (Mardani et al 2009). They reported that mechanical sideeffects remain a problem following construction of a total wrap, and are perhaps of even greater concern when the operation is performed laparoscopically.…”
Section: Division Versus Non Division Of the Short Gastric Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some measures have been proposed to prevent these surgery-related complications such as mobilization of the gastric fundus by complete division of short gastric vessels to create a floppy wrap. In a randomized study it was found that both dividing and preserving the short gastric vessels provided long term reflux control with no differences in QoL between the two approaches (Mardani et al, 2009). …”
Section: Symptomsmentioning
confidence: 99%
“…Der Nutzen oder Nachteil der Fundusmobilisierung wird sehr kontrovers unter Chirurgen diskutiert und wurde in einigen randomisierten Studien untersucht [16,17] …”
Section: Operationsindikationunclassified